Mitral Valve Replacement and Limited Myectomy for Hypertrophic Obstructive Cardiomyopathy: A 25-Year Follow-Up - Stassano, Paolo (2004)
Hypertrophic obstructive cardiomyopathy is a dynamic obstruction of the left ventricular outflow tract caused by septal hypertrophy and systolic anterior motion of the mitral valve. When the condition cannot be controlled by medical therapy, the most frequently used surgical approach is left ventricular myotomy-myectomy. Mitral valve replacement (to correct another mechanism of obstruction) is another surgical option; however, its use for this condition is controversial. We review the long-term results of patients who underwent limited left ventricular myotomy-myectomy and mitral valve replacement at our institution. Eighteen patients who had hypertrophic obstructive cardiomyopathy and severe mitral insufficiency underwent surgery between 1978 and 1983: 7 were men and 11 were women (mean age, 41.8 ± 10.5 years). Preoperatively, most of the patients (78.8%) were in New York Heart Association functional class III or IV. The operation consisted of a shallow myectomy of the hypertrophied septum and mitral valve replacement. One patient died in the hospital (5.5%); 3 patients died later during follow-up. The remaining 14 patients are alive and in good condition (mean follow-up, 21.9 ± 1.7 years). Functional class improved postoperatively in all surviving patients. The mean left ventricular outflow tract gradient fell from 78.1 ± 20.9 mmHg preoperatively to 9.4 ± 5.2 mmHg postoperatively (P < 0.001). At present, surgical treatment of hypertrophic obstructive cardiomyopathy does not include mitral valve replacement. However, our long-term results show that limited ventricular myectomy and mitral valve replacement predictably and consistently lower the left ventricular outflow tract gradient and resolve the mitral valve insufficiency.